Global trends of circular economy and innovation research: A bibliometric analysis - Mohd Rizal, Razalli; Mohd Kamarul Irwan, Abdul Rahim; Alminnourliza, Noordin; Abdul, Kafi; Lateh, Alawee; Muhammad Fakhrul, Yusuf; Muhammad Kashif, Shad (International Information and Engineering Technology Association, 2024)
In recent years, the circular economy has gained significant attention as a sustainable alternative to traditional linear production and consumption models. This study conducts a bibliometric analysis of circular economy and innovation literature from the Scopus database, covering 2016 to July 2024. Utilizing VOSviewer and Biblioshiny to create knowledge maps and visualizations for examining co-occurrence, co-authorship, and international collaboration patterns. The analysis of 401 documents revealed significant insights into current and emerging publication trends. Predominant author keywords included "circular economy", "innovation", "sustainable development", and "sustainability." The journal Sustainability (Switzerland) emerged as the leader in productivity, while Ecological Economics garnered the highest citation count. Notably, the United Kingdom ranked as the most productive country in this field. The thematic evaluation maps highlighted a concentration on critical research topics such as development of sustainable business models, technological advancements for waste valorisation, product design and innovation, collaborative innovation networks, policy and regulation-induced innovation, and digital transformation for circular economy. The findings can contribute researchers, policymakers, and industry leaders regarding the transition to a circular economy through innovation to achieve Sustainable Development Goals (SDGs).